Risk of potential exposure incident in non-healthcare workers in contact with infectious and municipal waste - Kanisek, Sanja (Zdravstveno varstvo, 2018)
Introduction: The proper classification of sharp and infectious waste in situ by the healthcare workers is an important measure of prevention of sharps and other exposure incidents in non-healthcare workers, who handle such waste. The aim was to examine the practice of classifying sharp and infectious waste in family and dental practices. Methods: An analysis of 50 bags of infectious and 50 bags of municipal waste from five family and five dental practices for five days in October 2016 at the Health centre Osijek. Results: Healthcare workers in 70% of the practices deposited sharps in infectious waste. In 56% of infectious waste bags, sharp object were found. More risky bags of infectious waste were produced by family practices (64%), but with no significant differences in relation to dental practices (48%), (P=0.143). Disposing of infectious into municipal waste was the case in 90% of the practitioners, where in 60% of municipal waste bags, infectious waste was disposed. Dental practices produced more risky bags of municipal waste (76%) in relation to family practices (44%), but with no significant difference (P=0.714). Conclusions: The results of this research point to importance of performing audits of proper disposal of sharps and infectious waste to reduce the risks of injury to non-healthcare workers who come into contact with the said waste. Given results could be used for framing written protocols of proper disposal of sharps and infectious waste that should be visibly available in family and dental practices and for education of healthcare workers
Keywords: injuries; medical waste; medicinski odpadki; poškodbe; primarna zdravstvena zaščita; primary healthcare